Multicentre Evaluation of KONE Optima Analysis System - Ferrero, Carlo; Modenese, Annalisa; Bonini, Pier Angelo; Ceriotti, Ferruccio; Carobene, Anna; Franzin, Michela; Guder, Walter G.; Hofmann, Walter; Puukka, Matti; Laitinen, Harri; Makarovsky, Vladimir; Gaidukova, Natalia; et al. (Clinical chemistry and laboratory medicine, 1998)
Optima from KONE Instruments Corporation is a new selective laboratory analyzer for turbidimetric, colorimetric and ion selective electrode measurements. Overall analytical performance of Optima and reagents provided by KONE was evaluated according to ECCLS guidelines, in a multicentre study involving four different laboratories, including substrates (cholesterol, high-density lipoprotein-cholesterol, creatinine), specific proteins (transferrin, IgG), enzyme activities (γ-glutamyltransferase, alanine aminotransferase) and electrolytes (sodium, potassium, chloride). The results obtained attest good precision of the system for all the analytes tested: the range of withinrun CV is 0.5%–4.3%, and range of between-day CV% is 0.8%–7.9% (median of four laboratories). Except for total cholesterol (5 % overestimation compared to the reference method) accuracy of measurement is adequate. Creatinine and uric acid assays were subjects of interference (defined as deviation > 10% from target value) by bilirubin and haemoglobin respectively.